Spin–valley dynamics in alloy-based transition metal dichalcogenide heterobilayers. (6th January 2021) - Kravtsov, Vasily; Liubomirov, Aleksey D; Cherbunin, Roman V; Catanzaro, Alessandro; Genco, Armando; Gillard, Daniel; Alexeev, Evgeny M; Ivanova, Tatiana; Khestanova, Ekaterina; Shelykh, Ivan A; Tartakovskii, Alexander I; Skolnick, Maurice S; et al.
Abstract: Van der Waals heterobilayers based on 2D transition metal dichalcogenides have been recently shown to support robust and long-lived valley polarization for potential valleytronic applications. However, the roles of the chemical composition and geometric alignment of the constituent layers in the underlying dynamics remain largely unexplored. Here we study spin–valley relaxation dynamics in heterobilayers with different structures and optical properties engineered via the use of alloyed monolayer semiconductors. Through a combination of time-resolved Kerr rotation spectroscopic measurements and theoretical modeling for Mo1 −  x W x Se2 /WSe2 samples with different chemical compositions and stacking angles, we uncover the contributions of the interlayer exciton recombination and charge carrier spin depolarization to the overall valley dynamics. We show that the corresponding decay rates can be tuned in a wide range in transitions from a misaligned to an aligned structure, and from a hetero- to a homo-bilayer. Our results provide insights into the microscopic spin–valley polarization mechanisms in van der Waals heterostructures for the development of future 2D valleytronic devices.